Growth Performance of Macrobrachium rosenbergii Post Larvae Fed with Vegetable Wastes and Palmolein Supplemented Formulated Feeds - P. Saravana Bhavan*, A. Anne Rebecca and (Recent Research in Science and Technology, 2011)
The possibility for utilizing massively-available vegetable wastes as one of the feed ingredients for better growth and survival of Macrobrachium rosenbergii was checked as these wastes are good sources for antioxidants and other nutrients. Vegetable waste powder (VWP) was prepared from dried potato peel, cabbage thick outer greens, peel of carrot, beetroot and cauliflower.Ã‚Â Basal ingredients (BI), such as coconut oilcake, groundnut oilcake and soybean meal (as protein sources), and rice bran and wheat bran (as carbohydrate sources) were powdered separately and taken in equal proportion. The VWP was incorporated with BI in different ratios (5%, 15% and 25%). Egg albumin and tapioca flour were used as binders. Vitamin B-complex was also mixed. The diet also contained Cod liver oil and palmolein in equal proportion as lipid sources. Palmolein, low cost oil was used to replace the high cost fish oil partially. A pinch of table salt was also added. These were subjected to pellet preparation. Feed without addition of VWP was served as control. Feeding trials were conducted for a period of 60 days on M. rosenbergii post larvae (PL). Significant increases in weight gain (WG), P<0.005, survival rate (SR), P<0.016, levels of biochemical constituents (total protein, amino acid, and ash), P<0.506,Ã‚Â indices of feed quality (feed intake and feed efficiency (FE) and indices of protein (protein intake, protein efficiency ratio (PER), protein conversion ratio (PCR) and protein productive value (PPV) were recorded in PL, particularly fed with 15% VWP incorporated formulated feed when compared with control (P<0.622). The digestibility of formulated feeds was found to be lower. This is because of rich fiber content due to addition of VWP. This in turn responsible for the higher fecal output recorded in experimental PL groups.Ã‚Â However, the food conversion rate (FCR), P<0.000 and protein assimilation rate (PAR), P<0.122 were found to be significantly decreased in experimental PL groups when compared with control. The results indicate the fact that the prawn has utilized the VWP effectively for growth. The higher carbohydrate content of VWP ensures sparing of protein for growth. Therefore, VWP can be included in feed formulation for developing sustainable aquaculture practices.